Bio-inspired generative design for support structure generation and optimization in Additive Manufacturing (AM). Issue 1 (2020) - Zhang, Yicha; Wang, Zhiping; Zhang, Yancheng; Gomes, Samuel; Bernard, Alain
Abstract : Additive Manufacturing (AM) is widely used to manufacture complex and personalized medical components. However, the generation and manually removing of support structures in the pre- and post-processing stages are still time-consuming and costly. To improve the automation of preparation while reducing support structure volume, post-processing time and cost, this paper proposes a bio-inspired generative design method, integrating parametric L systems, evolutionary optimization and an AM processing simulation model, to generate light-weight, easy-to-remove and heat-diffusion-friendly biomimetic support structures. Dental components are modelled and manufactured for validating the proposed method. The results obtained are compared with that of existing commercial software tools.